Soybean Recent Advances in Research and Applications - Ohyama, Takuji; Takahashi, Yoshihiko; Ohtake, Norikuni; Sato, Takashi; Tanabata, Sayuri (IntechOpen, 2022)
Increasing population and the expected decrease in crop production due to climate changes and land damage in near future may be rescued by changing from animal meat to plant protein, especially soybean protein. Recently, meat substitutes produced from soybean have become popular This book discusses recent advances in research and applications of soybean. Soybean seeds contain an extraordinarily high concentration of protein and oil, and the demand for soybean is increasing due to their nutritional value for both humans and livestock. Also, soybean has been used as biofuel in the replacement of petroleum oil. This book gives a comprehensive overview of soybean in five sections: "Role of Soybean for Food Security", "Physiology and Biochemistry of Soybean Plants", "Cultivation and Productivity of Soybean", "Breeding and Biotechnology of Soybean", and "Food and Biodiesel Industry".